2021
DOI: 10.1038/s41467-021-23375-7
|View full text |Cite
|
Sign up to set email alerts
|

Twin boundary defect engineering improves lithium-ion diffusion for fast-charging spinel cathode materials

Abstract: Defect engineering on electrode materials is considered an effective approach to improve the electrochemical performance of batteries since the presence of a variety of defects with different dimensions may promote ion diffusion and provide extra storage sites. However, manipulating defects and obtaining an in-depth understanding of their role in electrode materials remain challenging. Here, we deliberately introduce a considerable number of twin boundaries into spinel cathodes by adjusting the synthesis condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 63 publications
0
64
0
Order By: Relevance
“…Previous studies have indicated that ITB migration can also occur through the movement of this 9R structure [58]. While SFs serving as dislocation sources have rarely been reported in experiments, several important studies have also shown that TBs can significantly affect the physical and chemical properties of materials [60,61]. Thus, our results may also provide clues for understanding how and why the physical and chemical properties of materials usually change with different structures and boundaries [62,63], especially during deformation and practical application.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have indicated that ITB migration can also occur through the movement of this 9R structure [58]. While SFs serving as dislocation sources have rarely been reported in experiments, several important studies have also shown that TBs can significantly affect the physical and chemical properties of materials [60,61]. Thus, our results may also provide clues for understanding how and why the physical and chemical properties of materials usually change with different structures and boundaries [62,63], especially during deformation and practical application.…”
Section: Discussionmentioning
confidence: 57%
“…At the high voltage region (4.0–4.3 V), the Nyquist plots of both samples exhibit two distinct parts including a depressed semicircle in the high-frequency region and an inclined line in the low-frequency zone. The high-frequency semicircle should be related to the charge-transfer resistance 39 41 . By comparing the diameters of the semicircles in the high-voltage region (Supplementary Table 9 ), the impedances of CuMgTi-571 and NaMNO 2 are similar, implying similar electronic conductivity of the two de-sodiated samples.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Wang and coworkers prepared LiMn 2 O 4 with plenty of twin boundaries (LMO-TB) by varying the addition of lithium salt to understand the relationship between electrochemical properties and defects. 102 As illustrated in Fig. 3f and g, two types of twin boundaries (symmetrical and asymmetrical twinning) could be obviously observed in atomically resolved high-angle annular dark-field scanning transmission electron microscopy (HAADF STEM) images.…”
Section: Classification Of Defectsmentioning
confidence: 88%